Biorational Management of Red Ant (Dorylus orientalis Westwood) of Potato in Taplejung, Nepal - Bhatta, Madav; Thapa, Resham B.; Pokharel, Min R.; Sharma, Moha D. (Journal of the Plant Protection Society, 2018)
Red ant (Dorylus orientalis Westwood) has long been known as an important pest of potato in middle hills of Nepal. Several management approaches against this pest were studied in Fungling VDC-4 of Taplejung district in 2012. Field efficacy of botanicals (Artemisa, Eupatorium, Agave, Justicia, and Azadirachta) @ 1.44 kg/plot and chemical chlorpyrifos (pyrifos 20 EC @ 2 ml/litre of water) as treatments with four replications were tested using the susceptible variety, Kufri Jyoti. The application of agave was effective to reduce the damage by 42.93 ± 1.20% as compared to control i.e. 68.39±0.62%. Among all the treatments, the application of chemical insecticide, chlorpyrifos gave lower mean yield damage than the control plot. These findings can be verified and applied for the management of red ant of potato under farmers' field condition.